LUTEOLIN PROTECTS AGAINST VASCULAR INFLAMMATION IN MICE AND TNF-ALPHA-INDUCED MONOCYTE ADHESION TO ENDOTHELIAL CELLS VIA SUPPRESSING IΚBα/NF-κB SIGNALING PATHWAY - Jia, Zhenquan (J Nutr Biochem, 2014)
Vascular inflammation plays a significant role in the pathogenesis of atherosclerosis. Luteolin, a naturally-occurring flavanoid, present in many medicinal plants as well as in some commonly consumed fruits and vegetables has received wide attention for its potential to improve vascular function in vitro. However, its effect in vivo and the molecular mechanism of luteolin at physiological concentrations remain unclear. Here, we report that luteolin as low as 0.5 μM significantly inhibited TNF-α-induced adhesion of monocytes to human EA.hy 926 endothelial cells, a key event in triggering vascular inflammation. Luteolin potently suppressed TNF-α-induced expression of the chemokine monocyte chemotactic protein-1 (MCP-1) and adhesion molecules ICAM-1 and VCAM-1, key mediators involved in enhancing endothelial cell-monocyte interaction. Furthermore, luteolin inhibited TNF-α-induced NF-κB transcriptional activity, IκBα degradation, expression of IκB kinase ß (IKKß), and subsequent NF-κB p65 nuclear translocation in endothelial cells, suggesting that luteolin can inhibit inflammation by suppressing NF-κB signaling. In an animal study, C57BL/6 mice were fed a diet containing 0% or 0.6% luteolin for three weeks and luteolin supplementation greatly suppressed TNF-α-induced increases in circulating levels of MCP-1/JE, CXCL1/KC, and sICAM-1 in C57BL/6 mice. Consistently, dietary intake of luteolin significantly reduced TNF-α-stimulated adhesion of monocytes to aortic endothelial cells ex vivo. Histology shows that luteolin treatment prevented the eruption of endothelial lining in the intima layer of the aorta and preserved elastin fibers’ delicate organization as shown by Verhoeff-van Gieson staining. Immunohistochemistry studies further show that luteolin treatment also reduced VCAM-1 and monocyte-derived F4/80-positive macrophages in the aorta of TNF-α-treated mice. In conclusion, luteolin protects against TNF-α-induced vascular inflammation, in both in vitro and in vivo models. This anti-inflammatory effect of luteolin may be mediated via inhibition of the NF-κB-mediated pathway.